1985
DOI: 10.1038/315382a0
|View full text |Cite
|
Sign up to set email alerts
|

Direct mutagenesis of Ha-ras-1 oncogenes by N-nitroso-N-methylurea during initiation of mammary carcinogenesis in rats

Abstract: Induction of mammary carcinomas in rats by a single exposure to a carcinogen during sexual development often involves malignant activation of the Ha-ras-1 locus. Each of the Ha-ras-1 oncogenes present in tumours induced by N-nitroso-N-methylurea, but not in those induced by 7,12-dimethylbenz(a)anthracene, became activated by the same G----A transition, the type of mutation induced by N-nitroso-N-methylurea. These results are consistent with the notion that Ha-ras-1 oncogenes are directly activated by the carci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

26
352
2
5

Year Published

1987
1987
2005
2005

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 786 publications
(385 citation statements)
references
References 21 publications
26
352
2
5
Order By: Relevance
“…In contrast, subgroup analysis of specific point mutations in the K-ras gene showed that high consumption of meat products is positively associated with rectal tumours harbouring a G4A transition. Although the association was not statistically significant, this observation is in line with the biological evidence (Zarbl et al, 1985;Topal, 1988;Jacoby et al, 1992;Hughes et al, 2001;Bingham et al, 2002). Why the association in our study is confined to the rectum and not to the colon remains unclear.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…In contrast, subgroup analysis of specific point mutations in the K-ras gene showed that high consumption of meat products is positively associated with rectal tumours harbouring a G4A transition. Although the association was not statistically significant, this observation is in line with the biological evidence (Zarbl et al, 1985;Topal, 1988;Jacoby et al, 1992;Hughes et al, 2001;Bingham et al, 2002). Why the association in our study is confined to the rectum and not to the colon remains unclear.…”
Section: Discussionsupporting
confidence: 87%
“…Alkylating DNA agents like nitrosamines could generate O 6 -methylguanines and these have been detected in human colonic tissue (Hall et al, 1991). N-nitroso compounds could also induce G4A transitions in codons 12 or 13 of the K-ras gene of rat colon carcinomas (Zarbl et al, 1985;Topal, 1988;Jacoby et al, 1992) or in human colonic tissue (Hughes et al, 2001;Bingham et al, 2002). In the current study, no clear association was observed for daily consumption of meat products and overall colon and rectal cancer risk.…”
Section: Discussionmentioning
confidence: 99%
“…Previously, MNU has been shown to induce G : C to A : T mutations in N-ras codon 61 in rat mammary tumors (Zarbl et al, 1985;Cha et al, 1994) and in K-ras codon 12 (GGT) in mouse lymphomas (Corominas et al, 1991). Thus, in mice, there should be a correlation between the number and type of mutations induced by MNU and activation of K-ras in the resulting lymphomas.…”
mentioning
confidence: 98%
“…A large body of evidence indicates that several factors, including endogenous metabolites and exogenous carcinogen compounds can induce DNA damage (Zarbl et al, 1985). The nature and the location of the mutational change within the TP53 gene di er greatly among tumors of di erent histological type which may be a re¯ection of some DNA genotoxic agents (Greenblatt et al, 1994).…”
mentioning
confidence: 99%